25-Gauge Vitrectomy Combined with Half-Fluence Photodynamic Therapy for the Treatment of Juxtapapillary Retinal Capillary Hemangioma: A Case Report - Mariotti, Cesare; Giovannini, Alfonso; Reibaldi, Michele; Nicolai, Michele; Saitta, Andrea (Case reports in ophthalmology, 2014)
A rare case of juxtapapillary retinal capillary hemangioma (JRCH) with tractional macular detachment that was managed successfully with minimally invasive 25-gauge vitreoretinal surgery, followed by two sessions of half-fluence photodynamic treatment (PDT) with good visual outcome, is presented. A 13-year-old female patient had progressive deterioration of the vision of her right eye due to the presence of tractional macular detachment associated with JRCH in von Hippel-Lindau (VHL) disease. A 25-gauge sutureless vitreoretinal surgery was successfully performed. Two months following surgery, the JRCH was treated with two sessions of half-fluence PDT at an interval of 4 months. Visual acuity improved from a preoperative level of 20/50 to 20/25 24 months postoperatively. Resolution of the tractional macular detachment, reduction of papillomacular area fluid, and reduction in size of the JRCH were observed during the follow-up period. No serious adverse events were observed. Small-gauge vitreoretinal surgery followed by PDT can be effective and safe in relieving tractional macular detachment and recovering useful visual acuity in JRCH in VHL disease.